USING ULTRASOUND DIAGNOSTICS AND MAGNETIC RESONANCE TOMOGRAPHY IN SURGICAL TREATMENT OF COMPLICATED FORMS OF ACUTE PARAPROCTITIS - Shevchuk, I.M.; Novitsky, O.V.; Shapoval, A.L.; Sadovyi, I.Ya.; Sverstyuk, A.S.; Snizhko, S.S. (World of Medicine and Biology, 2022)
The results of surgical treatment of 134 patients with ischiorectal and pelviorectal acute paraproctitis were analyzed. Among them 81 (60.4 %) were men, 53 (39.6 %) were women aged 19 to 78 years. Ischiorectal acute paraproctitis was diagnosed in 71 (52.9 %), retrorectal – in 21 (15.8 %), pelviorectal – in 17 (12.7 %), horseshoe – in 16 (11.9 %), panparaproctitis (pelvic phlegmon) – in 9 (6.7 %) patients. The use of ultrasound and magnetic resonance imaging for the diagnosis of acute paraproctitis was analyzed in 67 (50.0 %) patients. Establishing the location of the abscess in the pararectal cell spaces, visualization of the primary purulent course and the affected crypt, permitted performing primary radical surgery in 79.1 % (53/67) of patients in the main group. In the comparison group, primary radical surgery was performed in 48 % (32/67) of patients. According to the Bayesian formula, the probability of complications during non-radical surgery in the main group of patients was 0.31, and in the comparison group ‒ 0.43. The probability of no complications during non-radical surgery in the main group of patients was 0.69, and in the comparison group ‒ 0.57, which confirmed the efficacy of ultrasound and magnetic resonance imaging in the diagnosis and treatment of patients with acute paraproctitis in the main group, relative to the comparison group.